Genetic Characterization of a Model Ciliopathy: Bardet–Biedl Syndrome - Kops, Samantha A.; Kylat, Ranjit I.; Bhatia, Shanti; Seckeler, Michael D.; Barber, Brent J.; Bader, Mohammad Y. (Journal of Pediatric Genetics, 2020)
Bardet–Biedl syndrome (BBS) is a rare ciliopathy affecting multiple organ systems. Patients with BBS are usually diagnosed later in childhood when clinical features of the disease become apparent. In this article, we presented a case of BBS discovered by whole genome sequencing in a newborn with heterotaxy, duodenal atresia, and complex congenital heart disease. Early diagnosis is important not only for prognostication but also to explore ways to mitigate the cone–rod dysfunction and for exploring newer therapies. Our case highlights the importance of a high index of suspicion and the utility of advanced genetic testing to provide an early diagnosis for a rare disease.
Keywords: Bardet–Biedl Syndrome; ciliopathies; whole genome sequencing; stem cell therapy; heterotaxy syndrome